Анна Каренина: [роман] / Лев Толстой - Толстой Лев Николаевич (Русская классика, 2020)
Экземпляры: (20210715) / Инвентарный номер: 41667 / Цена: 205.81 / Сис.шифр: 84(2=411.2) / Авт.знак: Т 53 / ГРНТИ: 17 / ББК: 84(2=411.2)